Pies & prejudice - Frederick, Heather Vogel (The Mother-Daughter Book Club, 2010)
Four girls, and their mothers, continue their mother-daughter book club via videoconference between Massachusetts and England, reading Jane Austen's "Pride and Prejudice," and try to put friendship before romance.